The influence of compensation, work motivation, organizational culture, leadership, and work discipline on employee performance at PT Adiartha Swabuana Batam - Yenni Melyani; Sri Langgeng Ratnasari; Firdaus Hamta (Journal of Applied Business Administration, 2026)
This study aims to analyze the influence of compensation, work motivation, organizational culture, leadership, and work discipline on employee performance at PT Adiartha Swabuana Batam partially or simultaneously. The study uses a quantitative approach with an explanatory survey design. The population is all employees of PT Adiartha Swabuana Batam as many as 60 people, and the entire population is used as a sample using saturated sampling techniques (census). Data were collected using a questionnaire with a five-point Likert scale, then analyzed using multiple linear regression assisted by IBM SPSS Statistics 25. The results showed that partially all variables had a positive and significant effect on employee performance, namely compensation (t = 5.134; sig. = 0.000), work motivation (t = 5.149; sig. = 0.000), organizational culture (t = 2.256; sig. = 0.026), leadership (t = 8.448; sig. = 0.000), and work discipline (t = 9.289; sig. = 0.000). Simultaneously, all five variables had a significant effect on employee performance (F = 5.300; sig. = 0.000) with an Adjusted R² of 0.267, which means that the five independent variables together explain 26.7% of the variation in employee performance. The effects are, however, distributed unevenly: work discipline is by far the most dominant variable (β = 0.766), followed by compensation (β = 0.318), leadership (β = 0.272), and work motivation (β = 0.271), while organizational culture is the weakest predictor in the model (β = 0.085). This study was limited to one oil and gas EPCM company in Batam with a sample size of 60 respondents, so the generalization of the findings needs to be done carefully. Practically, management needs to prioritize strengthening work discipline, compensation, and leadership as a strategic step to improve performance, and to sustain work motivation, which also contributes substantially; by contrast, organizational culture calls for a change of approach rather than additional investment, with the intended values embedded in the operating procedures and project routines that actually govern behaviour in the oil and gas project industry. The novelty of the research lies in the context of the oil and gas EPCM (Engineering, Procurement, Construction, and Manpower Service) industry in Batam which is still rarely studied empirically in the human resource management literature in Indonesia.